Estimates of Initial Coefficients in Some Subclasses of Analytic and Bi-Univalent Functions - بدور, حسن; علي, محمد; عياش, مجد (Tishreen University Journal -Basic Sciences Series, 2021)
In this paper, we present an estimate for the Fekete-Szegö inequality in the subclass which is defined by Frasin. This estimate led to improving the bound of the third coefficient in this subclass and in the subclass .